Geological services in the Lesser Antilies - Tomblin, John (My University, 2010)
This paper outlines the Geological services available in the Caribbean with special emphasis on the services offered by the Seismic Research Unit.
Paper presented at the Commonwealth Geological Liaison Office seminar on Geological services in the Caribbean.
Keywords: Seismic Research Unit; services